Effect of Aerobic Exercise on Hematological Parameters of Football Players at University Level - Muhammad Imran; Samreen Abid; Reema Aman; Haider Zaman; Taj Mali Khan; Fakiha Wadiat; Saman Gul (Al-Qanṭara, 2023)
Physical activities play an active role in the hematological parameters of human body. These changes have been found to involve in enhancement of Red Blood Cells (RBCs), White Blood Cells (WBCs) and Platelets depending on nature of exercise. Duration of exercise and intensity of the exercise also fluctuate these parameters. This study's primary goal was to examine the influence of aerobic exercise (one mile run) on hematological parameters of the football players participated in intervarsity sports competition during the year of 2021-22 from the Gomal University Dera Ismail Khan (KPK), Pakistan. The voluntarily participating individuals were divided into two groups of similar size, the Experimental Group (EG, n=15), and the Control Group (CG, n=15). One mile run test was given to experimental group while control group untreated. Keeping in view the nature of research design pre-post experimental design the researcher get the hematological parameters before and after the completion of 8 week aerobic exercise program. Auto-analyzer was used to obtain the results of hematological parameters. The anthropometric measurement along with pulse rate, diastolic and systolic blood pressure of the participant was measured. For the purpose of statistical analysis The data were evaluated using the t-test Additionally, after the completion of 8-week exercise program the Pulse rate, BMI, Diastolic BP, Systolic BP, WBCs, RBCs and Platelets of the EG was improved as compared to the CG. Key words: Hematological Parameters, Aerobic Exercise, Pulse Rate.